The Influence of Self-Depersonalization Technique in Alleviating Anxiety in Students with Drug-Addicted Parents - Alfin Siregar Siregar (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
Students raised in families with drug-addicted parents often face heightened anxiety due to unstable and neglectful home environments. This study investigated the effectiveness of the self-distancing technique a cognitive approach encouraging reflection on emotions from a third-person perspective in reducing anxiety among these students. Using a quasi-experimental pretest-posttest control group design, 18 students were divided equally into experimental and control groups. Anxiety was measured with a validated and reliable questionnaire (r = 0.680–0.889; Cronbach’s α = 0.947). Despite non-normality (Shapiro-Wilk, p < 0.05), parametric tests were applied given the small sample size, with homogeneity confirmed (Levene’s test, p = 0.812). Results showed a significant reduction in anxiety in the experimental group (Paired Sample T-Test, p = 0.001; mean difference = 16.67) and significant differences between groups (Independent Sample T-Test, p = 0.000). The findings indicate that self-distancing effectively alleviates anxiety and can be integrated into school counseling programs as a culturally adaptable intervention to enhance students’ emotional well-being. Keywords: anxiety in students, drug-addicted parents, self-depersonalization